2011
DOI: 10.1186/1748-717x-6-9
|View full text |Cite|
|
Sign up to set email alerts
|

An ultrasonographic evaluation of skin thickness in breast cancer patients after postmastectomy radiation therapy

Abstract: BackgroundTo determine the usefulness of ultrasonography in the assessment of post radiotherapy skin changes in postmastectomy breast cancer patients.MethodsPatients treated for postmastectomy radiotherapy in National University Hospital (NUH) and Tan Tock Seng Hospital (TTSH), Singapore between January 2004- December 2005 was recruited retrospectively. Ultrasound scan was performed on these Asian patients who had been treated to a total dose of 46-50 Gy with 1 cm bolus placed on the skin. The ultrasound scans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
0
20
0
2
Order By: Relevance
“…It also negatively affects the quality of life of patients . Reducing the frequency and severity of this event can be beneficial to patients and result in immediate improvement in comfort but also decrease the risk of certain rare and delayed events such as chronic radiation dermatitis, carcinoma, and sarcomas, although the link between acute and late radiation dermatitis is not fully established …”
Section: Introductionmentioning
confidence: 99%
“…It also negatively affects the quality of life of patients . Reducing the frequency and severity of this event can be beneficial to patients and result in immediate improvement in comfort but also decrease the risk of certain rare and delayed events such as chronic radiation dermatitis, carcinoma, and sarcomas, although the link between acute and late radiation dermatitis is not fully established …”
Section: Introductionmentioning
confidence: 99%
“…For example, Warszawski et al as well as Huang et all. observed the thickening, while Wong et al reported thinning within irradiated skin . According to us, those discrepancies could be caused by natural evolution of fibrotic process in the skin.…”
Section: Discussionmentioning
confidence: 82%
“…So far, just a few studies have reported on usefulness of USG in the assessment of radiation dermatitis . Except one, most of those researches included exclusively patients with breast cancer . Their results indicated that thickening of the irradiated areas of the skin correlates with more severe skin reactions .…”
Section: Discussionmentioning
confidence: 99%
“…The VA scale used for this study was developed specifically to grade subtle erythematic changes in the subject's skin within the ROI. More widely used clinical assessment tools for skin toxicities including Common Terminology Criteria for Adverse Events (CTCAE), and Radiation Therapy Oncology Group (RTOG) were too coarse and did not suit the needs of this study [13,19].…”
Section: Erythema Model and Study Designmentioning
confidence: 99%